Ascensão política de Paulo Marinho em Caxias na década de 1980 - Pereira, Francisco das Chagas da Cruz (2017)
This paper aims to portray the political rise of Paulo Marinho in Caxias, as well as the importance of printing in this process. Paulo Marinho still has a political leadership in CaxiasMA, but his political emergence happened in the 1980s, when the Caxian society mobilized, claiming their rights, wanting a decent and better life. Marinho joined the PMDB and, with the party, created a political speech full of messages of hope. Its main project was to renew the political frameworks of the time, giving opportunity to young people and voice to the the poor people. The main idea of his proposals was that the "new" would supplant the "old" - synonymous of economic delay and linked to the dictatorial regime begun in 1964. Marinho and his party attracted thousands of followers who, in the great majority, identified in these proposals a condition of a better future. The rise of Paulo Marinho is undoubtedly the result of the social mobilization of the caxienses.